2023
DOI: 10.31362/patd.1249471
|View full text |Cite
|
Sign up to set email alerts
|

The relations of vitamin D receptor gene polymorphisms with risk of obesity, metabolic syndrome, hepatostetosis in Turkish children

Abstract: Purpose: The aim of study was to determine the relation of vitamin D receptor gene (VDR) polymorphisms of TaqI (rs731236), ApaI (rs7975232), BsmI (rs1544410), FokI (rs10735810) with the risk of obesity, metabolic syndrome and hepatosteatosis in children.Materials and methods: 130 obese and 130 healthy children of age range between 10-16 years included in this study. Anthropometric measurements, biochemical evaluations and abdominal USG of all children were done. Obese and healty children were analyzed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Additionally, those with the b/b genotype had higher BMI and HOMA-IR than those with the B/B and B/b genotypes. A study in obese children in Turkey found that BsmI polymorphism had a positive effect on the formation of obesity, metabolic syndrome, and hepatosteatosis 23 . However, some studies have not observed significant relationships between the VDR BsmI variant and obesity-related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, those with the b/b genotype had higher BMI and HOMA-IR than those with the B/B and B/b genotypes. A study in obese children in Turkey found that BsmI polymorphism had a positive effect on the formation of obesity, metabolic syndrome, and hepatosteatosis 23 . However, some studies have not observed significant relationships between the VDR BsmI variant and obesity-related parameters.…”
Section: Discussionmentioning
confidence: 99%